Probiotic Potential of Lactobacillus Strains with Antifungal Activity Isolated from Animal Manure - Soundharrajan Ilavenil; Hyung Soo Park; Mayakrishnan Vijayakumar; Mariadhas Valan Arasu; Da Hye Kim; Sivanesan Ravikumar; Ki Choon Choi (The Scientific World Journal)
The aim of the study was to isolate and characterize the lactic acid bacteria (LAB) from animal manure. Among the thirty LAB strains, four strains, namely, KCC-25, KCC-26, KCC-27, and KCC-28, showed good cell growth and antifungal activity and were selected for further characterization. Biochemical and physiology properties of strains confirmed that the strains are related to the Lactobacillus sp.; further, the 16S rRNA sequencing confirmed 99.99% sequence similarity towards Lactobacillus plantarum. The strains exhibited susceptibility against commonly used antibiotics with negative hemolytic property. Strains KCC-25, KCC-26, KCC-27, and KCC-28 showed strong antifungal activity against Aspergillus fumigatus, Penicillium chrysogenum, Penicillium roqueforti, Botrytis elliptica, and Fusarium oxysporum, respectively. Fermentation studies noted that the strains were able to produce significant amount of lactic, acetic, and succinic acids. Further, the production of extracellular proteolytic and glycolytic enzymes, survival under low pH, bile salts, and gastric juice together with positive bile salt hydrolase (Bsh) activity, cholesterol lowering, cell surface hydrophobicity, and aggregation properties were the strains advantages. Thus, KCC-25, KCC-26, KCC-27, and KCC-28 could have the survival ability in the harsh condition of the digestive system in the gastrointestinal tract. In conclusion, novel L. plantarum KCC-25, KCC-26, KCC-27, and KCC-28 could be considered as potential antimicrobial probiotic strains.